Jaccoud’s Arthropathy and Mitral Stenosis: a Complex Interplay in a Patient with Systemic Lupus Erythematosus - Azhar Ul Hassan; Asif Manzoor; Aneela Amjad; Muhammad Waleed Hassan; Wajahat Alam Lodhi; Muwahhid Rasheed (Pakistan Armed Forces Medical Journal, 2026)
Jaccoud’s arthropathy is a painless rheumatological condition characterized by non-erosive joint abnormality. Rheumatic heart disease has been rarely associated with Jaccoud’s arthropathy. A case of a young patient with a history of severe shortness of breath and joint deformity diagnosed as systemic lupus erythematosus (SLE) and mitral stenosis along with Jaccoud’s arthropathy has been described. This case highlights the importance of the complex association of Jaccoud’s arthropathy and rheumatic heart disease and its management.